A CULTURE OF AGRICULTURE FOR SUSTAINABLE PROSPERITY: A Prophetic Voice of Wendell Berry - Leena P Kuriakose (Journal of Dharma, 2021)
This paper casts light on Wendell Berry’s holistic approach to establishing sustainable societies worldwide by promoting a culture of agriculture and fostering prosperity. Sustainable prosperity becomes apprehensive in contemporary society, marked by inequalities and wars within and among nations, and sustainable development appears ambiguous. Berry believes humans should recognize their role as guardians of the earth and live in partnership and solidarity with all living beings. He critiques the modern era’s dominant principles of acquisitiveness, self-centeredness, and short-sightedness, as well as the destructive aspects of prosperity, justice, and peace. His arguments have an essential role in this society when we envision the Planetary Management mission primarily through the SDGs – Responsible Consumption and Production (SDG 12) and Climate Action (SDG13) according to SDG 2030 agenda. This paper analyses the possibility of maintaining sustainable prosperity through a culture of agriculture, where one does not denigrate human labour, lose family farms, and destroy nature for economic development. The ethical interface of this paper emphasizes that everyone should consider it imperative to safeguard natural harmony, food security, and people’s wellbeing; without which sustainability becomes questionable and impossible.